2016
DOI: 10.1186/s12864-016-3332-8
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided identification of a Hevein-like antimicrobial peptide of bell pepper leaves for biotechnological use

Abstract: BackgroundAntimicrobial peptides from plants present mechanisms of action that are different from those of conventional defense agents. They are under-explored but have a potential as commercial antimicrobials. Bell pepper leaves (‘Magali R’) are discarded after harvesting the fruit and are sources of bioactive peptides. This work reports the isolation by peptidomics tools, and the identification and partially characterization by computational tools of an antimicrobial peptide from bell pepper leaves, and evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
(83 reference statements)
0
5
0
1
Order By: Relevance
“…carotovora in a strain- and concentration-dependent response and mentioned that peptide compounds could be used as a biotechnological alternative for biological control of phytopathogens. Similarly, Dias-Games et al [ 52 ] showed that the Hevein-like peptide extracted from bell pepper leaves showed antimicrobial properties against Clavibacter michiganensis spp. michiganensis (Gram-positive) and Ralstonia solanacearum (Gram-negative).…”
Section: Biological Activities Of Bell Pepper Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…carotovora in a strain- and concentration-dependent response and mentioned that peptide compounds could be used as a biotechnological alternative for biological control of phytopathogens. Similarly, Dias-Games et al [ 52 ] showed that the Hevein-like peptide extracted from bell pepper leaves showed antimicrobial properties against Clavibacter michiganensis spp. michiganensis (Gram-positive) and Ralstonia solanacearum (Gram-negative).…”
Section: Biological Activities Of Bell Pepper Extractsmentioning
confidence: 99%
“…Additionally, Dias-Games et al [ 52 ] isolated a Hevein-like peptide from the leaves of bell pepper crops. These compounds showed antibacterial and antifungal activities and exhibited great potential for biotechnological use [ 53 ].…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
“…Although many AMPs are a part of the constitutive defense [ 1 , 2 , 3 , 7 , 10 , 36 ], insecticidal proteins were of significant interest in this study due to the relatively limited literature available. To investigate these oftentimes inducible AMPs, only plant tissue that was directly wounded by insect feeding was collected.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested that peptide discovery be aided by statistical testing in large protein databases. Peptides are very small compounds [6]. The researcher used the YOLO-V5 algorithm to determine the type of plant disease affecting bell pepper plants.…”
Section: Literature Surveymentioning
confidence: 99%